Psychological climate of class – factor for prevention and reduction of school aggressiveness - Georgescu, Ioana-Corina; Guțu, Vladimir (CEP USM, 2024)
Current research and studies demonstrate that the problem of bullying-type aggressiveness in school is worsening internationally as well as nationally. Various factors that lead to aggressiveness and violence among students are extensively analyzed, including non-vulnerable factors. In recent decades, the focus has been on addressing the problem of bullying in school that is becoming complex and difficult to realize. In the given article, an attempt is made to address the issue of reducing and preventing student aggression by valorizing the values and functions of the students’ class and, above all, the healthy psychological climate. Namely the psychological climate creates a favorable environment for learning and education that strongly influences the behavior of students. The characteristics of psychological climate, the ways of forming a healthy psychological climate, principles and ways of valorizing the classroom climate in preventing and reducing aggressiveness and bullying-type aggressiveness in school are analyzed. Some forms and methods of carrying out this process were also described. The proposed concept opens up new perspectives for preventing and reducing aggressiveness, including bullying in educational institutions.

Cercetările și studiile actuale demonstrează că problema agresivității de tip bullying în școală se agravează pe plan international, dar și national. Se analizează pe larg diferiți factori care duc la agresivitate și violență a elevilor inclusiv și factorii nonvulnerabili. În ultimile decenii accentul se pune pe abordarea problemei bullyingului în școală care devine una complexă și greu de rezolvat. În articolul dat se încearcă de a aborda problema diminuării și prevenirii agresivității elevilor, valorificând valențele și funcțiile clasei de elevi și în primul rând climatul psihologic sănătos. Anume climatul psihologic crează un mediu favorabil de învățare și educație care influențează puternic comportamentul elevilor. Se analizează caracteristicile climatului psihologic, modalitățile de formare a climatului psihologic sănătos, principii și modalități de valorificare a climatului clasei în prevenirea și diminuarea agresivitățiii și agresivității de tip bullying în școală. Se descriu și unele forme și metode de realizare a acestui proces. Conceptul propus deschide noi perspective de prevenire și diminuare a agresivității, inclusiv celei de tip bullying în instituțiile de învățământ.
Climatul psihologic al clasei - factor de prevenire și reducerea agresivității școlare
Keywords: psychological climate; aggressiveness; violence; bullying; educational environment; emotional state; mental health; school performance; climat psihologic; agresivitate; violență; mediu educațional; stare emoțională; sănătate mintală; performanță școlară